Notice that, since the first term is (x+2)^2, we dealing with a hyperbola that is parallel to the x-axis and centered in (-2,3).
The general form of a hyperbola centered in (c,d), and parallel to the x-axis is:
![((x-c)^2)/(a^2)-((y-d)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/l3ia91u0iuhoxc035ejdpehsmsf15f2odm.png)
Where a is the horizontal distance between the center of the hyperbola and the vertices.
Then, in our case:
![\begin{gathered} (-2,3)\to\text{center} \\ a=\pm4 \\ \Rightarrow(-2-4,3)=(-6,3),(-2+4,3)=(2,3)_{} \\ \text{are the vertices} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r60vce6rl56r99h8f76hzvhwsbzclspnmo.png)
The answer is (-6,3) and (2,3), the second option